Some new fixed point theorems for generalized weak contraction in partially ordered metric spaces. Issue 5 (14th July 2020) - Gupta, Vishal; Mani, Naveen; Jindal, Jonty
Abstract : The main objective of our work is to establish unique fixed point results in partially ordered metric spaces with the help of generalized ( ψ, α, β ) ‐contractive mappings. An example and application to integral type contraction are given to support our result.